Common oral complications of head and neck cancer radiation therapy: mucositis, infections, saliva change, fibrosis, sensory dysfunctions, dental caries, periodontal disease, and osteoradionecrosis. (25th October 2017) - Sroussi, Herve Y; Epstein, Joel B.; Bensadoun, Rene‐Jean; Saunders, Deborah P.; Lalla, Rajesh V.; Migliorati, Cesar A.; Heaivilin, Natalie; Zumsteg, Zachary S.
Abstract: Patients undergoing radiation therapy for the head and neck are susceptible to a significant and often abrupt deterioration in their oral health. The oral morbidities of radiation therapy include but are not limited to an increased susceptibility to dental caries and periodontal disease. They also include profound and often permanent functional and sensory changes involving the oral soft tissue. These changes range from oral mucositis experienced during and soon after treatment, mucosal opportunistic infections, neurosensory disorders, and tissue fibrosis. Many of the oral soft tissue changes following radiation therapy are difficult challenges to the patients and their caregivers and require life‐long strategies to alleviate their deleterious effect on basic life functions and on the quality of life. We discuss the presentation, prognosis, and management strategies of the dental structure and oral soft tissue morbidities resulting from the administration of therapeutic radiation in head and neck patient. A case for a collaborative and integrated multidisciplinary approach to the management of these patients is made, with specific recommendation to include knowledgeable and experienced oral health care professionals in the treatment team. Abstract : Oral complications of radiation therapy to the head and neck can result in acute and long‐term deterioration in oral soft tissues and dentition. The presentation, prognosis, and strategies to manage the dental and nondental morbidities of radiation therapy to the head and neck are discussed in this manuscript.